Preparation and characterization of chitosan/agar blends: Rheological and thermal studies - El-Hefian, E.A.; Nasef, M.M.; Yahaya, A.H.; Khan, R.A. (Soc Chilena Quimica, 2010)
In this work, a number of mixture aqueous solutions of chitosan/agar (CS/AG) at different ratios (considering chitosan as the main component) were prepared. The theological properties i.e. shearing viscosity and shear stress of the blend solutions as a function of shear rate as well as the thermal properties of the blend films were investigated. Among the parameters studied were temperature, shearing time and storage time. Results showed that almost Newtonian behavior was observed at temperatures from 40 degrees C to 55 degrees C for the ratios 100/0, 90/10, 80/20 and 70/30. However, the proportions 60/40 and 50/50 showed a clear shear thinning behavior (pseudoplastic non-Newtonian behavior). It was also found that all the blend solutions obeyed the Arrhenius equation. In addition, the effect of shearing time on the shearing viscosity of all blends did not show any significant differences at all shearing times applied in this study except the proportion 50/50 wherein decreasing in shearing viscosity and shear stress was observed as the shearing time increased. Furthermore, different behaviors were observed for the blend solutions when the period of storage was extended to three weeks. The FTIR results and the differential scanning calorimetery (DSC) curves showed that the interaction between chitosan and agar can occur.